Allegiance in International Humanitarian Law : the duty of fidelity and the laws of armed conflict - Martínez, Manuel Galvis (Journal of Conflict and Security Law, 2024)
Allegiance is a legal concept that seeks to regulate the duty of fidelity of individuals towards states. A particularity of allegiance is the fact that it has been repeatedly used in treaty provisions, as well as interpretation of rules, in the field of International Humanitarian Law. The fields in which it has been introduced are quite broad, from rules relating to Prisoner of War status, to defining the relationship between occupiers and occupied population, passing through rules on Protected Personal status for civilians, the internment of enemy aliens, rules on the conduct of hostilities, and deserters. The article analyses both the meaning of allegiance and how it has been used in International Humanitarian Law revealing some useful instances as well as a set of inconsistencies and potential perils for its use.